A new iterative scheme with nonexpansive - Pham, Ngoc Anh (Springer, 2013)
In this paper, we suggest a new iteration scheme for finding a common of the solution set of monotone, Lipschitz-type continuous equilibrium problems and the set of fixed points of a nonexpansive mapping. The scheme is based on both hybrid method and extragradient-type method. We obtain a strong convergence theorem for the sequences generated by these processes in a real Hilbert space. Based on this result, we also get some new and interesting results. The results in this paper generalize, extend, and improve some well-known results in the literature. AMS 2010 Mathematics subject classification: 65 K10, 65 K15, 90 C25, 90 C33.